(untitled) (UUM Journal of Legal Studies, 2012)
Law is the accumulation of rational ideas in response to community development that was born based on the idea of universality and morality. The idea of universality provides a justification for the enactment of basic human freedoms and recognition of basic human rights in the life of the country. Similarly, the idea of morality is that moral principles are general and can be analyzed by human reason. The second idea is the essence of it is used as a basic idea about the nature of the formulation of law and justice as a legal the flow law functional purpose in looking at the law more focused on the facts of a field, social, cultural, political, and religion as factors that need to be a consideration in seeking legal solutions. Both streams are still evolving and are applied in various countries around the world. With regard to the transformation of Islamic law in national legal systems, it cannot be separated from these two streams of law that is through a systems approach and the approach to legislation. Keyword: Transformation of the law, politics of law, national legal system, System of national law